THE HISTOCHEMICAL DEMONSTRATION OF GLYCOGEN BY SILVER COMPLEXES - FLORES, LORENZO; ARZAC, JOSE PEDRO (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1963)
Statistical data are presented on scorpion poisoning in Mexico Data are given for the toxicity of various spp of scorpions, their geographic distr, and the number of cases of poisoning occurring monthly, 1940 through April, 1946 The monthly distr
TRANSACTIONS OF THE ENTOMOLOGICAL SOCIETY OF LONDON
Keywords: HISTOCHEMICAL DEMONSTRATION, GLYCOGEN, SILVER COMPLEXES; QUIMICA; HISTORIAS POR ESPECIALIDADES; HISTORIA DE LA QUIMICA